Evaluation method of oil saturation index OSI for shale oil reservoir based on well logging data - Tian, Han; Wu, Hongliang; Yan, Weilin; Feng, Zhou; Li, Chaoliu; Ren, Li; Xu, Hongjun (Frontiers in Earth Science, 2024)
Oil saturation index (OSI) serves as an important indicator for potential movable hydrocarbons evaluation of shale oil reservoirs, which is mainly obtained through rock pyrolysis experiments. In this study, a new method is proposed to continually and efficiently evaluate the OSI of shale by NMR logging. The development of movable hydrocarbons in shale reservoirs can be identified based on the OSI values, which are accurately acquired by experimental measurements of the total organic carbon (TOC) and rock pyrolysis. Later by NMR measurement, various bin porosities are obtained by T2 cutoff values. In order to build the relationship between OSI value and movable fluid porosity, it is important to determine the T2 cutoff value that corresponds to the movable fluid porosity precisely. Shale samples from the first member of the Qingshankou Formation ("Qing 1 Member") are experimented in this paper. The 2D NMR analysis of the shale samples in three different states (original, dried state at 105 ℃ , saturated kerosene) reveals that the corresponding movable fluid porosity T2 cutoff value is 8 ms. The NMR bin porosity with T2>8 ms has a good linear relationship with the OSI value of rock pyrolysis analysis, which reflects the OSI value effectively. The larger the bin porosity of T2 > 8ms, the higher the movable oil content of shale reservoir. The result is consistent with the understanding that oil is enriched in large pores of the Gulong shale. The bin porosity obtained by NMR logging can evaluate the vertical variations of movable hydrocarbon content in the geological formation continuously. Compared with the traditional experimental measurement of limited depth points, the new method has distinct advantages on avoiding the possibility of missing potential movable oil layers.